GENDER RELATIONS IN THE FAMILY OF THE PRIANGAN REGENT IN THE ERA OF THE DUTCH COLONIAL GOVERNMENT - Nisa Khoerunisa; Rendi Wandani (RADJA PUBLIKA, 2026)
Traditional gender constructs often adhere to a patriarchal system that places men in a position of dominance over women. These unequal relations occur in almost all social strata of society, including among the nobility. This study attempts to explore the patterns of gender roles that were formed within the families of the Priangan regents during the Dutch colonial period from 1800 to 1942. This study uses a descriptive qualitative case study method, collecting data from various literature in books, journals, newspapers, and websites related to the theme, which is then analyzed through a gender lens. The results show that men have a dominant role in family life, reflected in the rule that only men can become bureaucratic leaders, family leaders, and are free to practice polygamy. Meanwhile, women played the role of symbols of family honor who were tasked with appearing elegant, educating children, and being responsible for traditional activities such as celebrations or feasts. These gender relations were influenced by the construction of Javanese traditional values ​​through colonization during the Islamic Mataram Kingdom era, Dutch rules, and Islamic values ​​embraced by the Priangan nobility, which ultimately created a patriarchal gender ideology pattern that tended to marginalize women.